P–132 Centralized versus local embryologists scoring of blastocyst quality obtained in a large European multicenter clinical trial. (6th August 2021) - Montag, M; Va. de. Abbeel, E; Ebner, T; Larsson, P; Mannaerts, B
Abstract: Study question: Does blastocyst quality scoring by central assessment deviate from local assessment and potentially lead to the selection of a different single blastocyst for transfer? Summary answer: Central and local assessment provided the same quality classification (poor / good / top) in 69% of all blastocysts and 63% of all transferred blastocysts. What is known already: Blastocyst quality is scored most frequently by three morphological parameters, namely expansion and hatching (EH) status, inner cell mass (ICM) grading and trophectoderm (TE) grading. The score is used to define the quality classification (poor / good / top) which determines which embryo is to be transferred or cryopreserved. Blastocyst scoring and grading can be highly subjective, which does influence the choice for transfer and cryopreservation. Time-lapse imaging technology captures additional input about embryo development as well as enables centralized data storage and sharing for independent central assessments. Study design, size, duration: Pooled embryo analysis from a prospective, randomized, multicenter trial (RAINBOW) of 619 women undergoing ovarian stimulation with an individualized dose of follitropin delta in a long GnRH agonist protocol between May 2018 and January 2020. Blastocysts were centrally assessed using time-lapse images by two independent assessors and one adjudicator . Selection of the blastocyst for transfer by local assessment was based on morphological scoring and not on morphokinetic time-lapse parameters. Participants/materials, setting, methods: Oocytes were fertilized by ICSI and cultured in the Embryoscopeâ (Vitrolife) up to day 5 for transfer or day 5/6 for cryopreservation. Embryos were assessed as either non-blastocyst or blastocyst. Blastocysts were graded centrally and locally at 116 hrs of development, based on EH status (1–6), ICM (A-D) and TE grading (A-D). Central assessors were blinded to local assessment and embryo transfer selection. Main results and the role of chance: In total 4282 embryos were assessed centrally, of which 2046 day 5 embryos (48%) were adjudicated due to a scoring difference of at least one parameter between the two central assessors. In total 38% of day 5 embryos were judged as non-blastocysts and 62% as blastocysts of which 61% (i.e. 38% of all embryos) were determined to be of good or top quality. Identical results in terms of quality classification (poor / good / top) were obtained for 69% of blastocysts between local and central assessment and in 78%, between the two central assessors. Moreover, central and local scoring were identical in 62% for EH status, 53% for ICM grading and 57% for TE grading. For all transferred blastocysts (n = 508), central and local quality assessment was aligned for 63%. The ongoing pregnancy rate following single blastocyst transfer (SBT) was 41% (202/489), and similar to when considering only the transfers for which the central assessment had the same or a higher classification than the local assessment (166/411=40%). In 16% of all SBT, central quality assessment gave a lower score for the transferred blastocyst than the central assessment. This discrepancy could potentially have led to transfer of a different blastocyst. Limitations, reasons for caution: This trial included assessments made by embryologists from 20 IVF centres. Some centres has limited experience with time-lapse technology for morphological blastocyst scoring. Scoring could therefore have been affected by differences in focal planes, magnification and contrast compared to inverted microscopy, with potential influence on blastocyst scores and quality classification. Wider implications of the findings: Local and central blastocyst quality classification based on morphology aligns well but remains subjective. Embryo assessment may benefit from using tools like artificial intelligence-based algorithms for a more objective analysis. Trial registration number: NCT03564509